2013
DOI: 10.3996/032013-jfwm-026
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Survival of White-tailed Deer Fawns in Coastal South Carolina

Abstract: The social and environmental pressures exerted on white-tailed deer Odocoileus virginianus in the southeastern United States are dynamic. Understanding factors that contribute to neonatal white-tailed deer mortality is vital to population management. To determine survival rates and causes of mortality, we captured and radio-monitored neonate white-tailed deer in the coastal plain of South Carolina. Using date of birth, mass, sex, age, and year as predictor variables, we created a candidate set of survival mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…We used the best approximating model, as determined by Akaike's Information Criterion scores corrected for small sample size (AIC c ), from model set 1 as the underlying structure for all models in model set 2 (Burnham and Anderson 2002, Hill et al 2003, Zablan et al 2003, Rohm et al 2007). Intrinsic variables included in model set 1 were capture year, sex, birth mass, and birth date, all of which have been important in understanding neonatal deer survival in other regions (Rohm et al 2007, McCoy et al 2013). The effect of sibling status on neonate survival is unclear (Chitwood et al 2015b), and likely contributes little overdispersion to the data (Bishop et al 2008).…”
Section: Survival Model Developmentmentioning
confidence: 99%
“…We used the best approximating model, as determined by Akaike's Information Criterion scores corrected for small sample size (AIC c ), from model set 1 as the underlying structure for all models in model set 2 (Burnham and Anderson 2002, Hill et al 2003, Zablan et al 2003, Rohm et al 2007). Intrinsic variables included in model set 1 were capture year, sex, birth mass, and birth date, all of which have been important in understanding neonatal deer survival in other regions (Rohm et al 2007, McCoy et al 2013). The effect of sibling status on neonate survival is unclear (Chitwood et al 2015b), and likely contributes little overdispersion to the data (Bishop et al 2008).…”
Section: Survival Model Developmentmentioning
confidence: 99%
“…In areas where large canids or felids are absent, coyotes may suppress populations of smaller carnivores, thereby increasing abundance and diversity of songbirds and rodents (Levi and Wilmers ). Evidence also suggests coyotes are responsible for the majority of neonatal white‐tailed deer ( Odocoileus virginianus ) mortality in the Southeast (Saalfeld and Ditchkoff , Jackson , Kilgo et al , McCoy et al , Chitwood et al , Nelson et al ). Given the ability of coyotes to affect a wide variety of taxa including white‐tailed deer, the region's most pursued and economically important game species (U.S.…”
mentioning
confidence: 99%
“…Recently, numerous studies have quantified fawn survival in the presence of coyotes (Saalfeld and Ditchkoff 2007, Kilgo et al 2012, Jackson and Ditchkoff 2013, McCoy et al 2013, Chitwood et al 2015a, Nelson et al 2015, and most have shown that coyotes affect the number of fawns recruited into the huntable, fall population. Unfortunately, fawn survival studies are expensive and time-consuming, making them limited in spatial and temporal scope.…”
mentioning
confidence: 99%